2021
DOI: 10.1371/journal.pone.0257040
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and six-minute-walk test in patients after recovery from COVID-19: A prospective cohort study

Abstract: Objectives To study abnormality of spirometry, six-minute walk distance, and chest radiograph among patients recovered from Coronavirus Disease 2019 (COVID-19). Methods and study design A prospective cohort study was conducted in 87 COVID-19 confirmed cases who recovered and discharged from a medical school hospital in Thailand. At the follow-up visit on day 60 after onset of symptoms, patients underwent an evaluation by spirometry (FVC, FEV1, FEV1/FVC, FEF25-75, and PEF), a six-minute-walk test (6MWT), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
4
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 16 publications
5
39
4
6
Order By: Relevance
“…18 A previous prospective study in patients after recovery from COVID-19 found that those with severe pneumonia tended to have a non-statistically significant shorter mean 6MWT. 19 Even though we did not find an association between disease severity and walking distance, those with restrictive respiratory patterns had a shorter walking distance and were less likely to complete the test. While the exact role of the 6MWT in the follow-up of COVID patients has yet to be established, it can provide information on the impairment of daily activities and its correlation with peak oxygen uptake may indicate lung function.…”
Section: Discussioncontrasting
confidence: 69%
“…18 A previous prospective study in patients after recovery from COVID-19 found that those with severe pneumonia tended to have a non-statistically significant shorter mean 6MWT. 19 Even though we did not find an association between disease severity and walking distance, those with restrictive respiratory patterns had a shorter walking distance and were less likely to complete the test. While the exact role of the 6MWT in the follow-up of COVID patients has yet to be established, it can provide information on the impairment of daily activities and its correlation with peak oxygen uptake may indicate lung function.…”
Section: Discussioncontrasting
confidence: 69%
“…In some follow-up studies of hospital-based adult COVID-19 cohorts, persistent alterations of dynamic pulmonary function have been reported (41)(42)(43)(44). Results are conflicting though, as a relatively large adult study did not find any substantial alterations of spirometry tests results despite persistent radiological abnormalities (45), and two small cases series reported spirometry to be normal or near-normal in the aftermath of COVID-19 in children (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in COVID-19 survivors, the main pulmonary function abnormalities were a reduction in DLco with an almost normal DLco/VA and a reduction in FVC and TLC with an increase in the FEV 1 /FVC ratio [ 2 , 3 , 7 , 8 , 10 , 11 , 12 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower peripheral oxygen saturation (SpO 2 ) at rest and during the 6-min walk test (6MWT), total lung capacity (TLC), airway occlusion pressure after 0.1 s (P0.1) and P0.1/maximal inspiratory pressure (MIP) ratio were found in COVID-19 patients with pneumonia compared to those without pneumonia [ 7 ]. However, many studies [ 7 , 8 , 10 , 11 , 12 ] evaluated patients after 1 to 4 months from discharge and little information is provided about what happens in longer periods.…”
Section: Introductionmentioning
confidence: 99%